Možganska plastičnost in okrevanje kognitivnih funkcij - Čuš, Anja (Zdravniški vestnik, 2011)
Through its capacity of plastic changes, the adult brain enables successful dealing with new demands of everyday life and recovery after an acquired braindamage either spontaneously or by the help of rehabilitation interventions. Studies which explored the effects of cognitive training in thenormal population report on different types of changes in the performance of cognitive tasks as well as different types of changes in brain activation patterns. Following practice, brain activation can change in its extent, intensity or location, while cognitive processes can become more efficient or can be replaced by different processes. After acquired brain damage plastic changes are somewhat different. After the injury, the damaged brain area can either gradually regain its previous function, or different brain regions are recruited to perform that function. Studies of spontaneous and guided recoveryof cognitive functions have revealed both types of plastic changes that follow each other, as well as significant correlations between these changes and improvement on the behavioural level.
Keywords: Brain Diseases; Cognitive Dissonance; Cognitive Therapy; fiziologija; kognitivne sposobnosti; možgani; Možganske bolezni; Neuronal Plasticity; Nevronska plastičnost; obnavljanje; okvare; poškodbe; rehabilitacija; Spoznavno zdravljenje; vocational rehabilitation; Zaznavna neskladnost